PURCHASE CHANNEL SELECTION OF AGRICULTURAL MACHINERY BY WHEAT AND BARLEY FARMERS IN IRAQ: A TRANSACTIONS COST ATTITUDE - Mohammed A. M.; Zuhal R. Kadhim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to identify the role of transaction costs and their attributes in the selection of markets for the purchase of agricultural mechanization services in Baghdad province. To achieve this goal, a random sample of 150 wheat and barley farmers in the province was selected, and the data was collected through a questionnaire form prepared for this purpose. The research was based on the transaction cost theory as a modified theoretical framework to explain the farmer’s behavior towards choosing installment market channels to buy agricultural machinery and through the analysis of the binary logistic regression model. The results of the regression analysis showed that some elements of transaction cost, such as a privacy and uncertainty, have an important role in determining and choosing the installment market for the purchase of tractors, while the element of the number of repeat transactions proved its important role in choosing the installment market for seeders, and the time saving element showed its important role in choosing the installment market for combine harvesters. The results also showed the existence of significant differences in some demographic and economic characteristics related to farmer, such as farmer experience, farm area and net farm income, in influencing the respondents’ decision towards choosing the markets for agricultural machinery transactions referred to above.